Mudanças climáticas: o discurso da mídia sobre o aquecimento global - Zangalli Junior, Paulo Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This research is aimed at discussing the ways in which social agents influence global warming, analyzing the discourse of social actors involved in the debate on climate change, since there is a wide divergence in the scientific community about how man is able to modify the climate on a global scale. In fact the debate that permeates the issues beyond the limits of science and enter into a political-economic framework that takes extraordinary proportions. This emphasis can be very unscientific in the fundamental design concepts, or even creating a trivialization of the media. The main way to convey these concepts is to disclose them in the media, but the media has enormous power to transform the concepts and often manipulate the news by creating a common sense goes against the interests of the scientific community. Thus was conducted extensive research in major newspapers and magazines that move in the country. We surveyed the first two papers which were: “Folha de S. Paulo” and “O Estado de S. Paulo”, during the period from January 2000 to December 2008, totaling 3285 units for the newspaper Folha and 2555 for the newspaper Estadão. Subsequently a survey was made of data published in two journals that move at the national level, and these are the magazines VEJA and ÉPOCA for the same period. By performing these steps, it was concluded that several factors involving the media and climate change, such as topic relevance, types of approaches, perspectives of analysis, the staff development, supplies, among other factors of utmost importance for building news. As a result we can say that the media in fulfilling its role of mediator scientific, disclosing only a vision that permeates the scientific debate. The newspaper media, especially newspapers, has an informative and instantaneous. Often this preoccupation...(Complete abstract, click electronic access below)

Esta pesquisa tem como objetivo discutir as formas pelas quais os agentes sociais divulgam os temas relacionados ao aquecimento global, analisando os discursos dos principais atores sociais envolvidos no debate sobre a questão climática, visto que há uma grande divergência na comunidade científica sobre o quanto o Homem é capaz de modificar o clima em uma escala global. De fato o debate que permeia as questões extrapola os limites científicos e entram em um âmbito político-econômico que toma proporções extraordinárias. Esta ênfase não científica pode ser fundamental na concepção dos conceitos ou até mesmo criando uma banalização dos conteúdos. O principal meio de se veicular esses conceitos é divulgá-los na mídia, porém a mídia tem um poder enorme para transformar os conceitos e muitas vezes manipular as notícias criando um senso comum que contraria os resultados das pesquisas realizadas pela comunidade científica. Visto isso, foi realizada uma ampla consulta aos principais jornais e revistas que tramitam no país. Foram pesquisados a princípio dois jornais de grande circulação: “FOLHA DE SÃO PAULO” e “O ESTADO DE SÃO PAULO”, durante o período de janeiro de 2000 a julho de 2008, totalizando 3285 exemplares para o jornal Folha e 2555 para o jornal Estadão. Posteriormente foi feito um levantamento de dados em duas revistas de abrangência nacional, “VEJA” e “ÉPOCA” para o mesmo período. Ao se realizar estas etapas foi possível analisar vários fatores que envolvem a mídia e as mudanças climáticas, tais como: relevância conferida ao tema, tipos de abordagem, perspectivas de análise, desenvolvimento da pauta, fontes, dentre outros fatores de extrema importância para a construção de uma notícia. Como resultado, podemos afirmar...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geografia; Clima; Aquecimento global; Mídia; Agentes sociais; Mudanças climaticas; Climate Change; Social Agents; Media; Geography Climate; Global Warming